The effects of lecture-demonstration with self-learning methods on - Karbaschi, Roxana; Jacqueline Vartanoosian, Jacqueline (Advances in Nursing & Midwifery, 2012)
Abstract: Background and aim: New teaching methods have not received much attention in practical and laboratory classes for nursing students. With respect to the importance of nursing education , improving traditional methods of teaching and application of new methods are of concern. The aim of this study was to compare two teacher centered and active learning methods- lecturedemonstration with self-learning- in working with microscope in a group of nursing students in Shahid Beheshti Faculty of nursing and midwifery, Tehran Iran. Materials and Methods: 50 freshman students were selected and randomly assigned in two groups. After completing a demographic questionnaire, the students were taught microscopic application as a part of their physiology laboratory course. The contents were the same in the two groups but, in the self-learning method, the students were given educational pamphlet. Before and after session, students took part in an evaluation test for their learning. In addition, they were tested after 8 months for recalling evaluation. Data were analyzed by SPSS statistical software. Results: Findings showed that students ’ scores increased significantly in lecturedemonstration( 25.41) and self-learning(19.16) groups. In addition, no significant difference was found in the recalling of the two groups. In lecture-demonstration group, most of the students leveled on good and excellent echelon(62.5%) and in self-learning on intermediate and low echelon(68%). Conclusion: In general, both methods were effective in learning and recalling of nursing students with no significant difference. Keywords: Teaching method , lecture- demonstration , self-learning ,nursing students,